The greening of GE [alternative energy]. - Fairley, P.
General Electric (GE) Co., is now focused on alternative energy resources as it has begun manufacturing wind turbines and photovoltaics, invested in hydrogen fuel cells, and become a leader in the development of gasification equipment that could double the efficiency of coal-fired power plants and even capture their greenhouse gases. The company launched the ecomagination initiative, described as a growth strategy driven by the belief that applying technology to solving problems is good business. By focusing on wind, solar energy, and advanced coal technologies, GE plans to become a major force for environmental innovation.
Keywords: General Electric; Alternative energy resources; Coal-fired power plants; Ecomagination; Electricity generation market; Environmental innovation; Gasification equipment; Greenhouse gases; Hydrogen fuel cells; Photovoltaics; Wind turbines